The Role of Tax Modernization in Mediating the Relationship Between Tax Literacy and Tax Compliance of the Millennial Generation - Fifi Putri; Imarotus Suaidah; Siti Isnaniati (LP2M IAIN Palopo, 2026)
One of the key components in the tax system's efficiency and the long-term viability of government income is tax compliance. Taxpayer compliance is influenced by cognitive factors such as knowledge of tax laws and procedures, as well as by law enforcement and oversight measures. Tax compliance in the millennial taxpayer cohort is associated with tax literacy and taxpayer interaction with the tax administration system, which has undergone a technology-based revolution. The purpose of this study is to examine the impact of tax literacy on tax compliance and the role of tax modernization in mediating this association among millennial taxpayers. The study uses a quantitative approach with a survey method of 101 individual millennial taxpayers in Kediri City who have Taxpayer Identification Numbers and meet their tax obligations. The Sobel Test was used in conjunction with linear regression and mediation analysis to analyze the data. With an explanatory power of 54.4%, the study's findings demonstrate that tax literacy has a favorable and substantial impact on tax compliance. Tax literacy also has a beneficial and noteworthy impact on tax reform, accounting for 51.2% of the explanation. The multiple regression analysis shows that tax literacy and tax modernization, taken together, account for 56.2% of tax compliance. According to the Sobel test, tax literacy and tax compliance are partially mediated by tax modernization. Millennials' tax compliance, as evidenced by their adoption and use of the improved tax management system, appears to be impacted by their understanding of taxation